تقييم الأداء الاعلامي لمقدمي البرامج السياسية في القنوات الفضائية العراقية (Journal of Imam Al-Kadhim College, 2023)
Abstract:This research aims to find out the extent to which presenters of political programs in Iraqi satellite channels adhere to professional, ethical and responsibility standards from the point of view of academics in the field of media.  The importance of the research comes from the scarcity of studies that dealt with the media performance of program presenters, especially political ones, at the local level, which constitutes a new media source for researchers. The research reached results, the most important of which are:1/ The commitment of presenters of political programs in Iraqi satellite channels to professional media performance standards is generally high, at a rate of 76%.2/ The commitment of political program presenters in Iraqi satellite channels to ethical media performance standards is generally high, with a rate of 69.29%.3/ Commitment of presenters of political programs in Iraqi satellite channels to media performance standards in terms of social responsibility, with a high rate of 71.67%.
Keywords: الكلمات المفتاحية: تقييم الاداء, مقدمو البرامج , البرامج السياسية , القنوات الفضائية.